Occurrence and significance of polychlorinated biphenyls in water, sediment pore water and surface sediments of Umgeni River, KwaZulu-Natal, South Africa - Gakuba, Emmanuel; Moodley, Brenda; Ndungu, Patrick; Birungi, Grace (Environ Monit Assess, 2015)
The Umgeni River is one of the main sources of water in KwaZulu-Natal, South Africa; however; there is currently a lack of information on the presence and distribution of polychlorinated biphenyls (PCBs) in its sediment, sediment pore water and surface water. This study aims to determine the occurrence and significance of selected PCBs in the surface water, sediment pore water and surface sediment samples from the Umgeni River. Liquid-liquid and soxhlet extractions were used for water or pore water, and sediments, respectively. Extracts were cleaned up using a florisil column and analysed by gas chromatography-mass spectrometry. The total concentrations of eight polychlorinated biphenyls were 6.91–21.69 ng/mL, 40.67 252.30 ng/mL and 102.60–427.80 ng/g (dry weight), in unfiltered surface water, unfiltered sediment pore water and surface sediments, respectively. The percentage contributions of various matrices were 4, 36 and 60% for unfiltered surface water, unfiltered pore water and sediment, respectively. The highest concentrations of PCBs were found in water, pore water and Sediment collected from sampling sites close to the Northern Wastewater Treatment Works. The highest chlorinated biphenyl, PCB 180, was the most abundant at almost all sampling sites. To our knowledge, this is the first report on occurrence of polychlorinated biphenyls In the Umgeni River water, pore water and sediment system and our results provide valuable information regarding the partitioning of the PCBs between the water and sediment systems as well as the organic chemical quality of the water.
Keywords: Umgeni River; Sediment; Pore water; Polychlorinated biphenyls; Gas chromatography-mass spectrometry